Mixed compounds in code-switching contexts - Cristina Pierantozzi; Gloria Cocchi (LingBaW)
This pilot work analyses the acceptability of mixed compound words in code-switching contexts. In particular, we will discuss mixed Italian-German and Italian-English compounds, i.e. cases of mixing among languages where the process of compounding follows different rules for what concerns the position of the head, as well as inflection issues.